2020
DOI: 10.3390/children7090135
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Self-Concept and Discipline in Young Adolescents Who Practice Rhythmic Gymnastics. An Intervention

Abstract: This study aims to develop an intervention based on TARGET strategies in young people practicing rhythmic gymnastics, with the aim of observing whether motivation, discipline, self-concept and flexibility are improved. This research is a longitudinal study of a quasi-experimental nature. A total of 104 young adolescents between the ages of 11 and 12 years (11.66 ± 0.47) participated in the study, of which 60 belong to the control group and 44 to the experimental group. The intervention programme lasted two mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Looking at the variables that make up the task climate, it is observed that participants who show low adherence to the Mediterranean diet show higher scores than those who claim to have a medium or high adherence. Similar results were obtained by González-Valero et al [ 45 ] and Balaguer et al [ 46 ], who stated that the main reason for these results is that people who orientate their physical activity towards factors are not concerned about the care of their diet, as they do not require a high sporting performance. On the other hand, regarding the variables that make up the ego-climate, it is observed that those participants who show a high degree of adherence to the Mediterranean diet show higher scores.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Looking at the variables that make up the task climate, it is observed that participants who show low adherence to the Mediterranean diet show higher scores than those who claim to have a medium or high adherence. Similar results were obtained by González-Valero et al [ 45 ] and Balaguer et al [ 46 ], who stated that the main reason for these results is that people who orientate their physical activity towards factors are not concerned about the care of their diet, as they do not require a high sporting performance. On the other hand, regarding the variables that make up the ego-climate, it is observed that those participants who show a high degree of adherence to the Mediterranean diet show higher scores.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, looking at the relationships between physical self-concept and motivational climate, positive relationships are observed for low and medium adherence, but negative relationships are obtained for participants who show optimal adherence. Very distant results were found by González-Valero et al [ 45 ] where Conde-Pipó et al [ 51 ] state that a positive motivation towards activity practice has a positive impact on people’s physical self-image. However, Puertas-Molero et al [ 24 ] and Marfil-Carmona et al [ 25 ] point to the media as a discontent with the mental image that the person has of him/herself, affecting physical and mental health [ 52 ].…”
Section: Discussionmentioning
confidence: 91%
“…The before-mentioned is defined as the collection of beliefs about one’s self and is also associated with health behaviors [ 15 ], and following the multidimensional and hierarchical model proposed by Shavelson [ 20 ], it is divided into academic, social, family, emotional and physical dimensions [ 15 , 21 ]. The physical self-concept (PSC) is therefore the set of ideas that we believe define us physically [ 22 ], and is in turn made up of four other dimensions, physical condition (PC), sports competence (SC), physical attractiveness (AT) and physical strength (ST) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the reciprocal relationship between PA and PSC is widely documented [ 12 , 24 , 25 , 26 ], the evolution of PSC across a lifespan is not clear. Longitudinal studies are still scarce, with comparisons between age-groups prevailing, mainly focusing on child and adolescent stages, and there is no consensus on the results [ 13 , 14 , 22 , 27 , 28 , 29 ]. In studies that have addressed this issue in adulthood and old age, the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Physical self-concept (PSC) is defined as the set of ideas and abilities that we believe define us physically [25,26]. It is comprised of four subdomains: physical condition, sports competition, physical attractiveness and strength [27,28].…”
Section: Introductionmentioning
confidence: 99%